Effects of pulsatile secretion of growth hormone (GH) on fat deposition in human GH transgenic rats. Issue 2 (19th February 2013) - Furuhata, Yasufumi; Nishihara, Masugi; Takahashi, Michio
Abstract: Growth hormone (GH) is an endocrine regulator of glucose and lipid metabolism as well as body growth. GH levels are decreased and a unique pulsatile secretory pattern becomes obvious after puberty particularly in males. Coincidentally with this, males tend to deposit body fat. Experimental and clinical evidence has accumulated that obesity is associated with a decrease in GH levels. A strain of transgenic rats has been generated with severe obesity but normal nose-to-tail length, which has low circulating GH levels without pulsatility (human growth hormone (hGH) transgenic rats). The present review mainly focuses on recent and current work analysing the relationship between the occurrence of obesity and low GH levels and/or the absence of GH pulsatility in this transgenic animal model. This model has elevated blood glucose, non-esterified fatty acid, insulin and leptin levels associated with hyperphagia, suggesting that these rats also carry insulin- and leptin-resistant characteristics. hGH transgenic rats were subjected to a pair-feeding treatment to normalize food intake and chronic GH replacement to normalize GH levels. While the pair-feeding for 8 weeks successfully suppressed body-weight gain, the fat pad : body weight ratio remained very similar to freely-eating control hGH transgenic rats, which indicates the hyperphagia is not the sole contributor to the excess fat accumulation in this model. However, continuous elevation of peripheral hGH levels (approximately 2-fold) for 8 weeks by means of a slow-release vehicle resulted in a significant decrease in the fat mass : body weight ratios by 30 %. This GH treatment altered neither food intake nor body-weight gain. Thus, two characteristic phenotypes observed in the hGH transgenic rats, hyperphagia and obesity, seem to be closely related to GH levels and GH secretory pattern. This relationship might be working in the regulation of changes in seasonal body composition in wild animals.